2019
DOI: 10.1111/ajt.15572
|View full text |Cite
|
Sign up to set email alerts
|

Total parenteral nutrition in ex vivo lung perfusion: Addressing metabolism improves both inflammation and oxygenation

Abstract: Ex vivo lung perfusion (EVLP) protocols generally limit metabolic supplementation to insulin and glucose. We sought to determine whether the addition of total parenteral nutrition (TPN) would improve lung function in EVLP. Ten porcine lungs were perfused using EVLP for 24 hours and supplemented with insulin and glucose. In the treatment group (n = 5), the perfusate was also supplemented with a continuous infusion of TPN containing lipids, amino acids, essential vitamins, and cofactors. Physiologic parameters a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…This is in accordance to previous work which has been performed that showed that addressing metabolism through EVLP perfusate modification may improve donor lung quality. 26 , 27 , 28 , 29 Taken together with our findings, we believe that strategies that further promote metabolic recovery during the intermittent EVLP periods may prove to enhance our currently proposed protocol, which may lead to an extension of preservation periods significantly beyond 3 days.…”
Section: Discussionmentioning
confidence: 55%
“…This is in accordance to previous work which has been performed that showed that addressing metabolism through EVLP perfusate modification may improve donor lung quality. 26 , 27 , 28 , 29 Taken together with our findings, we believe that strategies that further promote metabolic recovery during the intermittent EVLP periods may prove to enhance our currently proposed protocol, which may lead to an extension of preservation periods significantly beyond 3 days.…”
Section: Discussionmentioning
confidence: 55%
“…The status of micronutrients and trace elements during ESOP and its association with inflammation and oxidative stress and outcomes of ex-situ organ preservation and transplantation has been almost unexplored so far. In a porcine model of extended ESLP for 24 hours, Buchko et al showed that continuous supplementation of the perfusate with the total parenteral solutions that also contain micronutrients, lead to lower inflammation, and improved graft function compared to the controls, however, the specific effects of the micronutrients/trace elements had not been explored (135). Also, to our best knowledge, there is no data available on the potential alterations in the levels of micronutrients and trace elements during ESHP, and implications of their decline, or supplementation on the preservation of the donated heart during ESHP, or the outcomes of transplantation.…”
Section: Absorption Of Antioxidants/ Decreased Antioxidative Potentialmentioning
confidence: 99%
“…After perfusing the lungs for 24 h, they found that TPN improved early graft function with substantial increase in oxygenation. 11 However, TPN creates the need for additional monitoring, costs, and complexity of the ex vivo perfusion system, complicating its clinical use.…”
Section: Introductionmentioning
confidence: 99%